Performance Test of Tuna Hand Fishing Line Hauler Tool by Using the Gear Ratio System Manually - Bachri, Samsul; Suyasa, I Nyoman; Soeboer, Deni Achmad (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
Problems with the operation of the hand line are that the fishing line is often entangled, fishermen are tired from going up and down the line and the large size of the tuna fish requires extra effort. The aim of the study was to find out whether the line hauler tool can solve problems in the operation of tuna handlines. Research time September to November 2022 in Sorong City. Catch data collection was carried out during research activities, the research method used experimental fishing. Experimental fishing was carried out with 2 treatments, namely control fishing line and handline with a line hauler for 16 trips/day. Control handlines had a total catch of 161 individuals, while handlines with line haulers had a total catch of 196 individuals. The results of the t test show that the use of the line hauler has an effect on the number of fishing gear settings. The effectiveness of the assistive devices can be seen from the different houling times between control lures and handlines with assistive devices, this time difference affects the number of settings produced during fishing gear operation, where the use of assistive devices results in a total of 196 settings and without tools 161 times setting. So the use of tools provides opportunities to get more fish compared to without tools. The value of the effectiveness of the use of assistive devices is 18%.